Using the Waterfall Model in Developing an Employee Payroll Information System - Hidayati, Nur (IJISTECH (International Journal of Information System and Technology), 2023)
Payroll is one of the most important elements in an organization, company or government agency, where remuneration is a right that must be given to employees for the performance and services they have provided during a certain period. Policies in managing payroll are certainly not the same from one company to another. Because each company has its own standards in determining the amount of salary that will be given to its employees. The most important thing is that the salary given must meet the Regional Minimum Wage  which has been determined by each region. Therefore, there needs to be good management in making payroll. However, currently there are still many organizations or companies that cannot manage their employee payroll well, because many still use conventional methods in calculating employee salaries. Under these conditions, of course it can cause problems. Problems that are often encountered include difficulties in recording employee salaries, delays in providing salaries to employees and inaccurate payroll reports produced. If this problem is allowed to continue, it will result in losses for employees. Therefore, to deal with this problem, it is necessary to develop a system with the hope that the resulting new system will be able to solve the problems faced in managing payroll. To support the development of this system, it is also necessary to select the right model that suits the needs of the organization or company. One of the models used is the Waterfall model. In the waterfall model, the stages that will be carried out in developing the system can be clearly identified, so that it is hoped that the final result will be an application that can be used in managing employee payroll information systems.